2020
DOI: 10.1111/nyas.14501
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and treatment options for gastroesophageal reflux disease: looking beyond acid

Abstract: Gastroesophageal reflux disease (GERD) is a disorder due to the retrograde flow of refluxate into the esophagus. Although GERD is a common clinical diagnosis, its pathogenesis is quite complex. As a result of its multifactorial development, many patients continue to experience adverse symptoms due to GERD despite prolonged acid suppression with proton pump inhibitor therapy. The pathogenesis of GERD involves an interplay of chemical, mechanical, psychologic, and neurologic mechanisms, which contribute to sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 100 publications
2
37
0
11
Order By: Relevance
“…Since the mechanisms through which each gastric content affects the occurrence of LPRD differ, the cause of the disease may vary depending on the speci c re ux content and its mechanism of action. However, the common phenomenon exhibited by these four contents is that they release ROS [21]. In the current study, using an in vitro model of LPRD, we found that acid exposure signi cantly increased the expression of ROS and MMP, which was reduced following treatment with the antioxidant, NAC, an ROS inhibitor.…”
Section: Discussionsupporting
confidence: 44%
“…Since the mechanisms through which each gastric content affects the occurrence of LPRD differ, the cause of the disease may vary depending on the speci c re ux content and its mechanism of action. However, the common phenomenon exhibited by these four contents is that they release ROS [21]. In the current study, using an in vitro model of LPRD, we found that acid exposure signi cantly increased the expression of ROS and MMP, which was reduced following treatment with the antioxidant, NAC, an ROS inhibitor.…”
Section: Discussionsupporting
confidence: 44%
“…However, the efficacy of PPI therapy is lower for patients with esophageal symptoms of GERD, and wanes even further for patients with extra-esophageal symptoms of GERD such as LPR [ 28 ]. One explanation for suboptimal symptom response to acid suppression relates to the well-established fact that symptoms of GERD are not all related to acid [ 20 ]. Regurgitation is a symptom perceived due to the mechanical flow of refluxate, regardless of acidity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite effectively suppressing gastric acid secretion, PPI therapy does not reduce the burden of gastroesophageal refluxate. Similar to concepts in gastroesophageal reflux disease (GERD), gastric refluxate is composed of bile and pepsin, which can injure esophageal and laryngeal epithelium, independent of acidity [ 20 ]. Thus, safe and less invasive treatment options beyond acid suppression are needed for LPR.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all cases of esophageal adenocarcinoma arise from underlying Barrett's esophagus, a metaplastic change in the esophagus [163]. Moreover, central obesity is involved in the pathogenesis and progression of Barrett's esophagus to esophageal adenocarcinoma [164,165] and GERD, a disorder due to the retrograde flow of refluxate into the esophagus [166]. Barrett's esophagus, esophageal adenocarcinoma, and GERD thus might be associated with adipokine alterations.…”
Section: Esophagusmentioning
confidence: 99%
“…The alteration patterns might act as diagnostic markers or therapeutic targets for specific digestive diseases. [171,185,186], stronger in men [166,172] Adiponectin I/D/N [184]/Among patients with GERD and among smokers [181], especially in patients with GERD [180,182]/ [186] Esophageal cancer Leptin I…”
Section: Adiponectinmentioning
confidence: 99%